Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1007/bf00003230
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diel cycle, tidal direction and trawl alignment on beam trawl catches in an equatorial estuary

Abstract: SynopsisUsing a 3 m beam trawl, catch variation in the fish and prawn assemblage of the Labu estuary, Papua New Guinea was investigated during July and December 1981 and September 1984. About six times more organisms, three and a half times the biomass and twice as many species were caught per trawl at night than during the day. The greatest number of species, individuals and biomass were caught just after dusk. With the exception of Secutor ruconius, there was no significant difference in the catches trawled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Behavioral studies show that many fishes are primarily active at night, searching for shelter during the day in inaccessible places to the net or in other protection areas. These fishes are rarely caught in diurnal samplings (QUINN;KOJIS, 1987). In the present study the major fish families presented different behavior in relation to the photoperiod.…”
Section: Discussionmentioning
confidence: 63%
“…Behavioral studies show that many fishes are primarily active at night, searching for shelter during the day in inaccessible places to the net or in other protection areas. These fishes are rarely caught in diurnal samplings (QUINN;KOJIS, 1987). In the present study the major fish families presented different behavior in relation to the photoperiod.…”
Section: Discussionmentioning
confidence: 63%
“…Since juvenile fish densities of all species groups whose juveniles were found in these areas were highest in the seagrass habitats, it is likely that seagrass habitats function as the most important juvenile habitats in areas outside the reef. In contrast to the high densities in seagrass habitats, the low fish densities and species richness in mangroves quantitatively support the suggestion that mangroves in the Indo-Pacific region are hardly used as a habitat by reef fish (Quinn & Kojis 1987, Robertson & Duke 1987, Thollot & Kulbicki 1988, Kimani et al 1996, Laroche et al 1997, Huxham et al 2004. A study in the Caribbean that used an approach comparable to that of the present study indicated that 30 of the 85 selected coral reef species used seagrass beds and mangroves as an important juvenile habitat (Nagelkerken et al 2000a).…”
Section: Species Groups and Habitat Utilisationmentioning
confidence: 58%
“…Mar Ecol Prog Ser 302: [63][64][65][66][67][68][69][70][71][72][73][74][75][76] 2005 relatively minor, and have concluded that there is less interaction between mangroves and other coastal habitats than in the Caribbean (Quinn & Kojis 1987, Robertson & Duke 1987, Thollot & Kulbicki 1988, Kimani et al 1996, Laroche et al 1997, Huxham et al 2004). Other studies, however, did report the presence of juvenile coral reef fish in mangrove areas (Lal et al 1984, Little et al 1988, Robertson & Duke 1990, Wakwabi & Mees 1999, de Boer et al 2001.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Gibson et al (1996) recorded the highest abundance of such fish at night, indicating an onshore migration at dusk followed by an offshore migration at dawn, which may have been determined by their feeding activity and predator avoidance. Quinn and Kojis (1987) found more species, individuals, and biomass immediately after dusk, probably due to changes in illumination, gear efficiency, and/or the behavior of the animals. Despite the diel changes in the occurrence of some species in the Nakdong River Estuary, no strong evidence for the existence of distinct day and/or night communities was identified.…”
Section: Discussionmentioning
confidence: 97%